Daya Tarik Wisata Waduk Gunungrowo di Kabupaten Pati, Jawa Tengah - Sugiarto, Eko; Prasetyo, Kinanti Ida Nursanti (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
Gunungrowo Reservoir in Sitiluhur Village, Gembong District, Pati Regency is one of the tourism destinations that is able to attract visitors with its tourist attractions. The purpose of this study is to identify and analyze the tourist attraction of Gunungrowo Reservoir both from the criteria and in terms of its relation to tourist activities. The theory used is the theory of tourist attraction. This research is a descriptive-qualitative. Primary data collection was done by observation and casual interview. Primary data collection was stopped when it reached the level of "redundancy" or obtained saturated data. Primary data that has been obtained is then analyzed and enriched with secondary data obtained from the search for documents relevant to the research topic. Based on the results of data analysis, it is concluded that the main attraction of Gunungrowo Reservoir is the beauty of the panorama that combines the beauty of the reservoir water with the background of the mountains and the sky when it is sunny. The beauty of Gunungrowo Reservoir is vulnerable because when the weather is not favorable, this beauty cannot be enjoyed. The beauty component of Gunungrowo Reservoir will also not be enjoyed when there is a long dry season that makes the reservoir water recede. Because the main attraction is vulnerable, Gunungrowo Reservoir is only suitable as a seasonal tourist destination, especially when the reservoir water conditions are abundant.